Digital protocol exocad in restorative dentistry: efficiency, personalization, and clinical predictability - Storoshchuk, Pavlo (Revista JRG de Estudos Acadêmicos, 2025)
Digital transformation in restorative dentistry has revolutionized clinical and laboratory workflows, providing greater accuracy, efficiency, and treatment predictability. Among the available technologies, Exocad (DentalCAD) stands out as one of the most versatile and widely used platforms, integrating intraoral scanning, cone-beam computed tomography (CBCT), facial imaging, and functional records within a single digital environment. This study conducted a narrative review with a critical and integrative approach, structured using the SALSA framework (Search, AppraisaL, Synthesis, and Analysis), covering publications from 2018 to August 2025. Searches were performed in the PubMed/MEDLINE, Scopus, Web of Science, ScienceDirect databases and institutional repositories of manufacturers and dental associations. The results indicate that Exocad use leads to a significant reduction in clinical and laboratory time, enhanced interdisciplinary communication, and greater esthetic and functional predictability of restorations compared to conventional methods. However, key limitations were identified, including high implementation costs, the need for continuous professional training, and a lack of long-term clinical studies. It is concluded that Exocad has a high disruptive potential in restorative dentistry, representing an essential tool for more efficient and personalized care, although its adoption must be supported by robust scientific evidence and standardized protocols.